Educating critical citizens? Portuguese teachers and students' visions of critical thinking at school. (September 2020) - Piedade, Filipe; Malafaia, Carla; Neves, Tiago; Loff, Manuel; Menezes, Isabel
Abstract: Recent attempts of online political manipulation using targeted political propaganda and fake news have reinforced critical thinking (CT) as a crucial component of a truly democratic active citizenship. This importance has led national and European authorities to increasingly incorporate CT into educational policies and recommendations, signaling schools as pivotal sites for its development. In this paper, we investigate how upper secondary teachers and students perceive the process of educating critical citizens in Portuguese schools. We have conducted 16 individual interviews with teachers and organized 8 focus group discussions with 61 students. The participants' discourses revealed that they believe that CT is only being marginally addressed in their classes. Both teachers and students identified overextended curricula and the excessive weight of evaluation as the major constraints for the development of pedagogical activities that are able to stimulate the students' CT in class. In this light, we conclude that the Portuguese educational system should either restructure the subjects' curricula or create extracurricular spaces in which CT could be intentionally encouraged. Additionally, we argue that, given the close connection between CT and active democratic citizenship, these activities could be integrated into strategies of citizenship education that may already be in place.